PERANCANGAN UI/UX WEBSITE TOPUR TRAINING & CONSULTING DENGAN MENGGUNAKAN METODE DESIGN THINKING: TOPUR TRAINING & CONSULTING WEBSITE UI/UX DESIGN USING THE DESIGN THINKING METHOD - Wildan Faujan Nugraha (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
ABSTRACT The digital world is constantly evolving, making it easier for people to do just about anything, including business. Information systems that help companies grow in the market are often the result of the use of information technology in business areas to cope with globalization. The pandemic has also had a major impact on consulting services firms At Topur Training & Consulting, we are required not only to provide information according to the customer's information collection needs, but also to design an attractive website interface. His UI/UX website design using Topur Training & Consulting design thinking method starts with Empathy, Definition, Idea, Prototype and Test followed by Usability phase using SUS method. Topur Training & Consulting's website appearance is operated in a prototype format for user convenience. Based on the results of processing her 5 respondents who achieved an average score of 83, Grade B on the usability test, we can say that this design is acceptable (accepted by users). The results obtained on the prototype website are included in the category of websites that have accepted conversion results from applying the SUS methodology in this study, according to the criteria for applying the System Usability Scale (SUS) methodology. Within the framework of this study, we were able to make recommendations for the design of the user interface of the Topur Training & Consulting website based on the results of evaluating user responses using the System Usability Scale methodology.